Repotrectinib in ROS1 Fusion-Positive Non-Small-Cell Lung Cancer - Drilon, Alexander; Camidge, D. Ross; Lin, Jessica J.; Kim, Sang-We; Solomon, Benjamin J.; Dziadziuszko, Rafal; Besse, Benjamin; Goto, Koichi; Langen, Adrianus Johannes de; Wolf, Jürgen; Lee, Ki Hyeong; Popat, Sanjay; et al. (The New England journal of medicine, 2024)
In this phase 1-2 trial, the TK inhibitor repotrectinib led to an objective response in 79% of patients with ROS1 fusion-positive NSCLC and no previous ROS1 TK inhibitor use. Median progression-free survival was nearly 3 years.